Enki and the World Order A Sumerian Myth - Cooper, Jerrold S. 1942- (Studies in Ancient Near Eastern Records (SANER), 2024)
"Enki and the World Order," a Sumerian myth from the early second millennium BCE, depicts the god Enki's reconstitution of the Sumerian world after an unspecified catastrophe. The myth ends with a face-off between Enki and the goddess of love and war, Inana, who is dissatisfied with Enki's allotment of functions to the other goddesses. This volume presents a critical edition of the 472-line Sumerian text, with introduction, translation and commentary, based on 25 published and unpublished manuscripts, mostly from Nippur in what is now southern Iraq. All the manuscripts, with one exception, have been collated, and there are many new fragments and joins to previously known tablets